A well-posedness and exponential decay of solutions for a coupled Lamé system with viscoelastic term and logarithmic source terms. Issue 7 (19th May 2021) - Boulaaras, Salah
Abstract : This paper describes a well-posedness and exponential decay of solutions for a coupled Lamé system with viscoelastic term and logarithmic source terms, where an asymptotic stability result of global solution is obtained.